LncRNA CALML3-AS1 regulates chondrocyte apoptosis by acting as a sponge for miR-146a - Tingting Nie; Chengqiang Zhang; Gailian Zhang; Lihua Fang; Xiaoping Liu; Rui Li; Luping Cui; Jie Wang (Taylor & Francis Group, 2021)
Chondrocyte apoptosis contributes to osteoarthritis, while miR-146a is a critical player in chondrocyte apoptosis. Our bioinformatics analysis showed that miR-146a may bind with long non-coding RNA (lncRNA) CALML3 antisense RNA 1 (CALML3-AS1). Our study was therefore carried out to investigate the interactions between lncRNA CALML3-AS1 and miR-146a in osteoarthritis. This study included 66 osteoarthritis patients who were admitted at Shanxi People's Hospital from July 2016 to June 2019. Transfections were performed to analyse gene interactions. RT-qPCR and Western blot were performed to determine the expression levels of gene and protein, respectively. Cell apoptosis of chondrocytes induced by lipopolysaccharide (LPS) was analysed by cell apoptosis assay. We found that CALML3-AS1 was downregulated, while miR-146a was upregulated in osteoarthritis. However, no significant correlation was found between them. In addition, overexpression of CALML3-AS1 or miR-146a did not affect the expression of each other. However, overexpression of CALML3-AS1 resulted in the upregulation of Smad family member 4 (Smad4), a downstream target of miR-146a. We also found that the expression of miR-146a and Smad4 were negatively correlated, while the correlation between CALML3-AS1 and smad4 was not significant. In cell apoptosis assay, overexpression of CALML3-AS1 and Smad4 resulted in decreased proliferation of chondrocytes. MiR-146a played an opposite role and reduced the effects of overexpression of CALML3-AS1 and Smad4. Therefore, CALML3-AS1 may regulate chondrocyte apoptosis by acting as a sponge for miR-146a to upregulate Smad4.